Use of Alternative Designs and Data Sources for Pediatric Trials. (2nd April 2020) - Cooner, Freda; Gamalo-Siebers, Margaret; Xia, Amy; Gao, Aijun; Ruan, Shiling; Jiang, Tony; Thompson, Laura
Abstract: Children are considered a vulnerable group and as such are granted additional protection as research subjects. Research projects using children as research subjects are justifiable if the answer to the scientific question of the study cannot be obtained by enrolling adult subjects (cf. scientific necessity ). Thus, there is an ethical obligation to explore innovative analytical strategies that seek balance between the feasibility of conducting a trial and maximizing the utilization of data on efficacy and safety. On this note, there is enthusiasm for implementing some less popular but efficient alternative designs for confirmatory pediatric trials. Within the pediatric extrapolation paradigm, examples of such designs, other than purely based on pharmacokinetic/pharmacodynamic data, are described in this article along with their advantages and disadvantages. This article will also discuss how to incorporate alternative data sources in the analysis of pediatric clinical trials. A discussion of existing approaches and a road-map to their utilization will be provided. Real case examples on the use of the approaches are provided.